2014
DOI: 10.1007/s00339-014-8355-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of polycrystalline CVD diamond films grown on fused silica optical fibres pre-treated by high-power sonication seeding

Abstract: In this paper, the growth of polycrystalline chemical vapour deposition (CVD) diamond thin films on fused silica optical fibres has been investigated. The research results show that the effective substrate seeding process can lower defect nucleation, and it simultaneously increases surface encapsulation. However, the growth process on glass requires high seeding density. The effects of suspension type and ultrasonic power were the specific objects of investigation. In order to increase the diamond density, gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The obtained diamond overlay is continuous and homogenous along the fiber (Fig. 2(b)), in agreement with previously obtained results on the fused glass slides [23,24]. Average crystallite size is between 100 and 200 nm (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The obtained diamond overlay is continuous and homogenous along the fiber (Fig. 2(b)), in agreement with previously obtained results on the fused glass slides [23,24]. Average crystallite size is between 100 and 200 nm (Fig.…”
Section: Resultssupporting
confidence: 80%
“…In our previous works, high power sonication seeding was applied to different suspensions (water/DMSO) in order to obtain diamond films on optical fibers [13]. We have observed that high power seeding can induce the erosion/cavitation of optical fibers.…”
Section: Introductionmentioning
confidence: 99%
“…It can be applied to various substrates [97][98][99], on large surfaces, up to eight inches [100,101]. Contrary to BEN, 3D substrates like silicon tips [102,103] or silica optical fibers [104] can be homogeneously coated [105]. The main challenge is the improvement of diamond films adhesion [20,93].…”
Section: Deposition Of Ndsmentioning
confidence: 99%